Teacher Learning Innovation in the Perspective of Principal Academic Supervision and Digital Literacy: An Empirical Study of State Junior High School in Tanah Datar Regency - Wirda Nengsih; Sulastri; Rusdinal; Irsyad (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Teacher learning innovation is increasingly important as schools respond to curriculum transformation and the growing use of digital technologies. However, innovative learning practices among public junior high school teachers remain uneven, indicating the need to examine both organizational support and teachers’ digital capabilities. This study investigates the effects of principal academic supervision and teacher digital literacy on learning innovation among public junior high school teachers in Tanah Datar Regency, Indonesia. A quantitative correlational design was employed involving 296 teachers selected from a population of 619 teachers through proportionate stratified random sampling. Data were collected using a five-point Likert questionnaire measuring academic supervision, digital literacy, and learning innovation, and were analyzed using prerequisite tests and multiple linear regression with IBM SPSS Statistics. The findings indicate that principal academic supervision was positively and significantly associated with teacher learning innovation, with an R² value of 0.481. Teacher digital literacy also showed a positive and significant relationship with learning innovation, with an R² value of 0.514. When examined simultaneously, the two predictors produced an R value of 0.762 and explained 58.1% of the variance in teacher learning innovation. The findings suggest that strengthening learning innovation requires more than improving teachers’ individual digital capabilities; it also depends on supportive academic supervision that encourages professional reflection and instructional improvement. The study highlights the importance of integrating instructional leadership and continuous digital competence development in efforts to strengthen innovative teaching practices.